Tradisi Masyarakat Muslim Dalam Membagi Harta Warisan Secara Kekeluargaan (Studi Di Kecamatan Jekan Raya Kota Palangka Raya) - Utami, Utami (IAIN Palangka Raya, 2016)
The background of the tradition of the muslim community in dividing the inheritance amicably was due to advice from one or more of the heirs which the most dominant in the division of inheritance,